Studying memory process in the brain - Maciejewska, Karina; Kłoskowicz, Małgorzata (No Limits, 2021)
How do we remember facts? Why do we forget some of them but remember others for years? What processes must take place for the memorization process to produce the desired results? Although scientists have been trying to discover all the secrets of our brain for years, we still do not know much about this organ. Knowledge of the processes taking place in the body of a healthy person can provide inspiration on how to look for ways of treating people with various neurological disorders and how to inhibit disease processes. Knowledge from neuroscience is also sometimes applied in sciences related to artificial intelligence, primarily in so-called machine learning.